2021
DOI: 10.1177/1477153521999592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coloured lighting on pleasure and arousal in relation to cultural differences

Abstract: This study examined the effects of lighting colour on emotional states and the effects of ethnicity on the impact of lighting colours on emotional states, based on the Mehrabian and Russell’s emotional state model measuring pleasure, arousal and dominance. It was hypothesised that there are significant differences in pleasure and arousal among six lighting colours: red, green, blue, yellow, orange and purple and that different ethnicities (i.e. Asian and Caucasian) can influence the effects of the six lighting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Jiarong Xie's office study of Biophilic Design and Blue Lighting found that blue-illuminated spaces led to lowered ratings in most perceived attributes [62]. H Lee, PhD, by examining the emotional impact of colored lighting on races with different cultural gaps, found that there was a significant effect of different races on the perception of light color but not on arousal, and that Asians were significantly less pleasant in red and purple lighting than all other colors and tended to feel happier than Caucasians, who were more unpleasant [63]. Ashwini Sunil Nair studied the effect of light colors in the built environment on the behavior of children with autism using many neutral tones, and pastel shades proved to be autism-friendly with a sedative and soothing effect, whereas bright, bold and strong colors resulted in behavioral changes in children with autism, who are prone to be sensitive to light [64].…”
Section: Emotional Responses To Colored Light In Spacesmentioning
confidence: 99%
“…Jiarong Xie's office study of Biophilic Design and Blue Lighting found that blue-illuminated spaces led to lowered ratings in most perceived attributes [62]. H Lee, PhD, by examining the emotional impact of colored lighting on races with different cultural gaps, found that there was a significant effect of different races on the perception of light color but not on arousal, and that Asians were significantly less pleasant in red and purple lighting than all other colors and tended to feel happier than Caucasians, who were more unpleasant [63]. Ashwini Sunil Nair studied the effect of light colors in the built environment on the behavior of children with autism using many neutral tones, and pastel shades proved to be autism-friendly with a sedative and soothing effect, whereas bright, bold and strong colors resulted in behavioral changes in children with autism, who are prone to be sensitive to light [64].…”
Section: Emotional Responses To Colored Light In Spacesmentioning
confidence: 99%
“…Emotional behavior of shoppers is affected by color and its combinations of a retail store, its display and merchandise (Bellizzi et al, 1983), hunters observe pleasure as a predictor to satisfaction (Floyd, 1997), satisfaction measurement study on "target-arousal level" provided knowledge regarding the key role of hedonic aspects (Wirtz et al, 2000) and supported the previous study by Berlyne (1970) on hedonic values and relationships between pleasantness, interestingness, and novelty. Pleasure and arousal are significant predictors when music is played at a location (Krause and North, 2016), effects of lighting color on emotional states (Lee and Lee, 2021). Research on online booking sites reveals the positive impact of e-atmospherics like portal design, music, and colorful effects on emotions that please hotel customers (Essawy, 2017).…”
Section: Visitors' Experiencementioning
confidence: 99%
“…The red environment can invigorate both physiologically and mental buyers and then weaken buying considerations and procurement choices he conjectured (Yildirim et al, 2015;Massara, 2020). Moreover, lighting had a major influence on the world so brilliantly illuminated spaces were more stirring than tiny lit rooms (Van Niekerk et al, 2016;Lee & Lee, 2021). observed, under "brilliant" light conditions, that customers reviewed and dealt with more of the things than under "bad" light conditions.…”
Section: Colour-lighting and Intention To Purchasementioning
confidence: 99%